GLIS Family Zinc Finger 1 was First Linked With Preaxial Polydactyly I in Humans by Stepwise Genetic Analysis - Jin, Jie-Yuan; Wu, Pan-Feng; Luo, Fang-Mei; Guo, Bing-Bing; Zeng, Lei; Fan, Liang-Liang; Tang, Ju-Yu; Xiang, Rong (Frontiers in Cell and Developmental Biology, 2022)
Background: Preaxial polydactyly (PPD) is one of the most common developmental malformations, with a prevalence of 0.8–1.4‰ in Asians. PPD is divided into four types, PPD I–IV, and PPD I is the most frequent type. Only six loci (GLI1, GLI3, STKLD1, ZRS, pre-ZRS, and a deletion located 240 kb from SHH) have been identified in non-syndromic PPD cases. However, pathogenesis of most PPD patients has never been investigated. This study aimed to understand the genetic mechanisms involved in the etiology of PPD I in a family with multiple affected members. Methods: We recruited a PPD I family (PPD001) and used stepwise genetic analysis to determine the genetic etiology. In addition, for functional validation of the identified GLIS1 variant, in vitro studies were conducted. GLIS1 variants were further screened in additional 155 PPD cases. Results: We identified a GLIS1 variant (NM_147193: c.1061G>A, p.R354H) in the PPD001 family. In vitro studies showed that this variant decreased the nuclear translocation of GLIS1 and resulted in increased cell viability and migration. RNA sequencing revealed abnormal TBX4 and SFRP2 expression in 293T cells transfected with mutant GLIS1. Additionally, we identified a GLIS1 variant (c.664G>A, p.D222N) in another PPD case. Conclusion: We identified two GLIS1 variants in PPD I patients and first linked GLIS1 with PPD I. Our findings contributed to future molecular and clinical diagnosis of PPD and deepened our knowledge of this disease.